Teachers voices on school reopening in Indonesia during COVID-19 pandemic - Avianto Amri (Elsevier, 2021)
The COVID-19 situation and school closure has brought intense impact to millions of students and teachers. However, there is a growing pressure from parents, teachers, and children for schools to reopen and the national government has developed guidelines if schools going to reopen. This study is conducted to assess the perspective of teachers and other education personnel regarding the current situation and the outlook when schools reopen in the future. A combination of survey, focus group discussions, and interviews were conducted among school personnel (i.e. teachers, school administrator, and school principals), local education office officials, and representatives from teacher's professional associations in Indonesia. A total of 27,046 school personnel participated in the survey, making it one of the largest surveys ever conducted with school personnel in Indonesia. In addition, 53 participants were involved in the FGDs and interviews in 5 areas. Findings suggest that 76% teachers were concerned if schools reopen due to the health risks and 95% teachers preferred having a blended learning or continue using full distance learning. Nevertheless, if schools reopen, teachers expressed the needs for greater health protection among teachers and children, strengthened coordination and collaboration with local stakeholders, and further capacity strengthening to ensure that the learning process can be safe, comfortable, and effective. Specific analysis on the perspective and needs for teachers working with special needs learners and disadvantaged areas are further analysed.